To investigate the individual and household-level factors influencing the willingness to pay for cataract surgery among patients aged 50 years and older in rural China: a cross-sectional study - Yaojiang Shi; Kang Du; Yuxiu Ding; Xiangzhe Chen; Hongyu Guan; Yunyun Zhang (BMJ Open)
Objectives To investigate the factors influencing the willingness to pay (WTP) for cataract surgery among patients aged 50 years and older in rural China at both individual and household levels.Design A cross-sectional study.Setting The study was conducted in Gansu, China.Participants Patients aged ≥50 years who were diagnosed with cataracts indicated for surgery and lived rural in Gansu from October to December 2020 were included in the study.Primary and secondary outcome measures The main study outcome was the patients’ WTP for cataract surgery. The association of individual characteristics, knowledge about cataracts, health status and household characteristics with patients’ WTP was also evaluated based on the collected data using structured questionnaires.Results A total of 324 (85.94%) patients in the study reported that they were willing to pay for their cataract surgery. However, only 179 (47.48%) patients were willing to pay over ¥1000 to cover the cost of cataract surgery under the New Rural Cooperative Medical System (NRCMS). Patients aged 75 years and older were significantly less likely to pay for cataract surgery (p=0.037). Better visual status (p=0.032), self-reported severe poor visual status (p=0.001), higher annual household income (p=0.052) and a higher level of children’s education (p=0.076) were significantly more likely to pay for cataract surgery.Conclusions The WTP for cataract surgery in rural China is still insufficient. More than half of patients’ WTP for surgery do not cover the cost of cataract surgery after reimbursement by the NRCMS. Both individual and household characteristics contribute to the low WTP for cataract surgery.